The Effect of Shear Stress on Armor Layer Thickness Under Steady Uniform Flow - Cahyono Ikhsan (Civil Engineering Journal, 2023)
The armor layer is essential for maintaining stability on riverbed surfaces. This layer forms when bedload sediment moves until the bed's surface erodes, resulting in a stable layer that reaches an equilibrium state where no further sediment transport occurs. Therefore, the objective of this study is to investigate the effect of grain size and shear stress on armor layer thickness using evenly mixed sand and gravel with five different grain size variations. The research methodology consists of laboratory experiments and optimization analysis. The main instrument used is a sediment-recirculating flume constructed from plexiglass, measuring 10, 0.60, and 0.45 m in length, width, and height, respectively. Bed slope varies across gradients of 1%, 1.4%, 1.8%, 2.2%, and 2.6%. The constant flow rate is set at capacities of 25 l/s, 30 l/s, 40 l/s, and 45 l/s. The results show the consistent behavior of the channel bed surface under different flow rate variations. Meanwhile, the variables affecting armor layer thickness are the uniformity coefficient (Cu), the difference in shear stress on the bed surface (τo-τc)/τc), beds shear stress, and the critical shear stress of the sediment grain. The primary novelty of this research is a formula to determine armor layer thickness. It showed that both shear stress and the proportion of sand-to-gravel materials play significant roles in the armoring process and subsequent changes in the riverbed. Doi: 10.28991/CEJ-2023-09-11-012 Full Text: PDF